Bureaucratizing the indigenous: The San peoples, Botswana, and the international community - Maria Sapignoli (Archivio Antropologico Mediterraneo)
This article examines the relationship between the San people and the post-colonial Botswana state as manifest in bureaucratic practices. These practices illustrate the dynamic between the state’s control and care toward its most discriminated groups and indigenous resistance, incorporation, and cooptation. It considers how Botswana, through the introduction of development policies and laws to regulate hunting, has encapsulated the San into state institutions and practices; it also illustrates, though the example of San activism, how indigenous peoples try to appropriate state institutions and international development models to formalize their resistance through non-governmental organizations. Bureaucratic processes have, on one hand, been experienced by the San as part of the problem of state-sponsored assimilation and control, while, on the other hand, they have been also utilized as part of the solution for seeking basic rights and recognition.